2008
DOI: 10.1007/s00340-008-3104-5
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the dielectric, optical and photorefractive properties of Sb-doped Sn2P2S6 crystals

Abstract: International audienceIn this work we report results on electro-physical, optical and photorefractive investigations for Sb-doped Sn2P2S6 crystals. The crystals are obtained by two methods: the vapour-transport technique and the Bridgman technique using stoichiometric Sn2P2S6 composition with different amounts of antimony in the initial compound. The good optical quality of the crystals obtained with the Bridgman technique is underlined. The dependences of the photorefractive two-beam coupling coefficient and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
9

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 11 publications
0
10
0
9
Order By: Relevance
“…15,18 The EPR-observed photocharging of a significant amount of Sb 3+ to Sb 2+ (on the order of 10 18 cm −3 ) is caused when electrons are transferred from intrinsic photorefractive centers in the Sn 2 P 2 S 6 crystals. After being formed, the photogenerated Sb 2+ ions act as hole traps.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…15,18 The EPR-observed photocharging of a significant amount of Sb 3+ to Sb 2+ (on the order of 10 18 cm −3 ) is caused when electrons are transferred from intrinsic photorefractive centers in the Sn 2 P 2 S 6 crystals. After being formed, the photogenerated Sb 2+ ions act as hole traps.…”
Section: Discussionmentioning
confidence: 99%
“…18 A significant increase in the photorefractive gain factor for red light correlates with the presence of this Sb-related optical absorption band and its associated photoconductivity. 15,18 More recently, preilluminated Sb-doped crystals have been shown to contain secondary photorefractive centers that affect the dynamics of the beam coupling and cause transient beam fanning. 20 Until the present study, no candidates for these Sb-related secondary centers have been identified.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, the photorefractive response of SPS is still inhibited by the space charge field limitation, a consequence of the insufficient effective trap density [5]. In part, the problem of insufficient effective trap density was solved by technological efforts: crystals deliberately doped during the growth procedure showed improved characteristics [3,6,7]. There remains, however, still much room for further improvement, until the fundamental limit for the gain factor is reached, which is defined by the largest Pockels tensor component of SPS.…”
Section: Introductionmentioning
confidence: 98%